Mathematical modeling of neutron radiography processes - Prokhorets, S.I.; Khazhmuradov, M.A. (Problems of Atomic Science and Technology, 2023)
A goal function is formulated and parameters for neutron radiography setup optimization are determined. The results of calculation of neutron passing through formation system are given. Сформульовано функцію мети та визначено параметри оптимізації установки нейтронної радіографії. Наведено результати розрахунку проходження нейтронів через систему формування.